Effects of Construction Time and Coarse Aggregate on Bridge Deck Cracking - Riding, Kyle A.; Poole, Jonathan L.; Schindler, Anton K.; Juenger, Maria C. G.; Folliard, Kevin J. (My University, 2009)
Bridge deck temperature changes in the first few days after placement due to the concrete heat of hydration and changes in ambient conditions have long been identified as a significant contributor to early-age cracking. The goal of this project was to develop a method of quantifying how materials and construction methods can influence the thermal stresses in bridge decks. A series of tests on concrete mixtures were then performed to quantify the concrete material thermal stress behavior in bridge decks with different placement times and coefficients of thermal expansion. Concrete with a high coefficient of thermal expansion placed in the morning led to the development of thermal stresses equal to 75% of the stress at cracking. It was also found that the thermal stresses could be reduced by up to 50% by using concrete with a lower coefficient of thermal expansion and placing at night.
Keywords: Bridge decks; Cracking; Thermal stresses